2021
DOI: 10.3390/su132011409
|View full text |Cite
|
Sign up to set email alerts
|

Application of Global Reporting Initiative (GRI) Principles for Measuring Quality of Corporate Social Responsibility (CSR) Disclosure: Evidence from Pakistan

Abstract: CSR Reporting is an essential mechanism for ensuring the transparency and accountability of companies towards sustainability performance. To further promote that sustainable development agenda, CSR-related regulations and policies have emerged worldwide, including in Pakistan. Therefore this study assesses the quality of corporate social responsibility in annual reports issued by firms listed at the Pakistan Stock Exchange. This study has operationalized the Global Reporting Initiative (GRI) principles for exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 67 publications
0
6
0
3
Order By: Relevance
“…GRI didirikan pada tahun 1997 dan sejak itu menjadi salah satu kerangka pelaporan keberlanjutan yang paling banyak digunakan di dunia (Corrêa & Ribeiro, 2020). Prinsip-prinsip GRI digunakan untuk menilai kualitas pengungkapan tanggung jawab sosial perusahaan (CSR), meliputi keseimbangan, keterbandingan, akurasi, kejelasan, keandalan, dan ketepatan waktu (Ismail et al, 2021). Penerapan kerangka GRI dapat memberikan manfaat bagi perusahaan, antara lain peningkatan transparansi dan akuntabilitas, peningkatan pengambilan keputusan, dan peningkatan reputasi (Constantin et al, 2020) Mandatory sustainability disclosure atau pengungkapan keberlanjutan wajib mengacu pada persyaratan bagi perusahaan untuk mengungkapkan informasi tentang kinerja lingkungan, sosial, dan tata kelola (ESG) mereka sebagai bagian dari kewajiban pelaporan mereka.…”
Section: Global Reporting Initiative Dan Mandatory Sustainability Dis...unclassified
“…GRI didirikan pada tahun 1997 dan sejak itu menjadi salah satu kerangka pelaporan keberlanjutan yang paling banyak digunakan di dunia (Corrêa & Ribeiro, 2020). Prinsip-prinsip GRI digunakan untuk menilai kualitas pengungkapan tanggung jawab sosial perusahaan (CSR), meliputi keseimbangan, keterbandingan, akurasi, kejelasan, keandalan, dan ketepatan waktu (Ismail et al, 2021). Penerapan kerangka GRI dapat memberikan manfaat bagi perusahaan, antara lain peningkatan transparansi dan akuntabilitas, peningkatan pengambilan keputusan, dan peningkatan reputasi (Constantin et al, 2020) Mandatory sustainability disclosure atau pengungkapan keberlanjutan wajib mengacu pada persyaratan bagi perusahaan untuk mengungkapkan informasi tentang kinerja lingkungan, sosial, dan tata kelola (ESG) mereka sebagai bagian dari kewajiban pelaporan mereka.…”
Section: Global Reporting Initiative Dan Mandatory Sustainability Dis...unclassified
“…Ashraf et al (2020) found that governance mechanisms improve sustainability reporting in the financial sector of Pakistan. Ismail et al (2021) found that organizations in Pakistan have less emphasis on CSR reporting based on GRI standards. Using stakeholders and legitimacy perspectives, Hongming et al (2021) found the increasing trend in sustainability reporting to build stakeholder trust and improve business legitimacy in society.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Specifically, Pakistan is a developing country with a different governance structure (Khan et al , 2019b) and corporate management and operations than developed countries (Khan et al , 2021). Existing studies that investigated corporate social responsibility (CSR) reporting (Ismail et al , 2021; Khan et al , 2019a) and sustainability reporting in the context of Pakistan (Khan et al , 2019b; Mahmood et al , 2019; Khan et al , 2021; Khan and Ghouri, 2022), ignored the sustainability reporting based on globally accepted GRI standards. Moreover, it is not clear from the previous literature what kind of sustainability reporting is preferred by organizations in Pakistan (Ahmad et al , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Standar pengungkapan Financial Accounting Standard Board (FASB), Global Reporting Initiatives (GRI), dan International Accounting Guidelines Board (IASB) untuk laporan tahunan membantu memberikan informasi yang seragam (IASB). Perusahaan biasanya menggunakan pedoman pelaporan keberlanjutan GRI karena menyediakan sistem pengkodean yang seragam untuk industri yang berbeda dan kerangka kerja pelaporan sukarela untuk semua jenis perusahaan (Ismail, Saleem, Zahra, Tufail, & Ali, 2021). GRI (Global Reporting Initiative) adalah organisasi multinasional independen yang membantu perusahaan dan organisasi lain untuk mengungkapkan dampaknya dalam bahasa global.…”
Section: Pendahuluanunclassified
“…Dua kelompok Prinsip Pelaporan GRI mendefinisikan konten dan kualitas laporan (Ismail, Saleem, Zahra, Tufail, & Ali, 2021). Ruang lingkup laporan ditentukan oleh aktivitas, dampak, serta harapan dan kepentingan substantif pemangku kepentingan, sesuai dengan pedoman isi laporan.…”
Section: Pendahuluanunclassified